1998
DOI: 10.1292/jvms.60.413
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Profile in Canine Pancreatitis Induced with Oleic Acid.

Abstract: ABSTRACT. Lipid and lipoprotein concentrations and apolipoprotein profile were investigated in canine pancreatitis induced by infusion with oleic acid (OA) into the accessory pancreatic duct. Pancreatitis was diagnosed by physical, hematological, biochemical and pathological examinations. In OA-treated dogs, serum triglyceride (TG) concentration was increased; however, there were no changes in serum total cholesterol (TC) and phospholipid (PL) concentrations. Serum concentrations of TG, TC, PL and total lipids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 19 publications
4
23
0
3
Order By: Relevance
“…SAA in dogs with and without systemic inflammation: The significant overlap performance of SAA demonstrated in the study confirms the results of previous studies of canine SAA [1,3,4,8], and extends the initial knowledge of the overlap performance of the LAT obtained as part of our validation of the assay [7]. Further, our comparison of the diagnostic performance of SAA with the performance of leukocytes, segmented and band neutrophils and body temperature suggests that routine measurements of SAA can be a useful adjunct to the information obtained by measuring these traditionally used inflammatory markers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…SAA in dogs with and without systemic inflammation: The significant overlap performance of SAA demonstrated in the study confirms the results of previous studies of canine SAA [1,3,4,8], and extends the initial knowledge of the overlap performance of the LAT obtained as part of our validation of the assay [7]. Further, our comparison of the diagnostic performance of SAA with the performance of leukocytes, segmented and band neutrophils and body temperature suggests that routine measurements of SAA can be a useful adjunct to the information obtained by measuring these traditionally used inflammatory markers.…”
Section: Discussionsupporting
confidence: 89%
“…Serum amyloid A (SAA) is a major positive APP in dogs, and marked increases in concentrations are consequently observed during the APR [3]. Studies in several species have shown that SAA is a more sensitive marker of systemic inflammation than traditionally used parameters such as body temperature, leukocyte and neutrophil counts [12,19], and SAA can be used as a diagnostic marker of systemic inflammation in several species, including dogs [1,4,8,21]. The commercial availability of diagnostic assays has, however, been limited to resource and time consuming methods, and so far measurements of canine SAA have not been implemented in routine veterinary clinical biochemistry [3].…”
mentioning
confidence: 99%
“…Existen muchas variables que pueden contribuir a la alteración del perfil lipídico de los caninos y, en consecuencia, a un aumento de este; entre estas variables se encuentra la obesidad, que se puede dar por numerosos factores, tanto ambientales como sociales, ya que la falta de ejercicio de los animales, la sobrealimentación o una dieta desequilibrada con una alimentación ad libitum de dietas ricas en grasa, la raza, la genética, la esterilización, medicamentos como los corticoesteroides y los progestágenos están relacionados como causantes de la obesidad (22). Por eso numerosos análisis identificaron que los perros obesos presentan un col-total, triglicéridos, col-VLDL, col-LDL, más alto que los caninos normales, mientras que el col-HDL es menor en los obesos presentándo-se una situación poco deseable por el riesgo de enfermedades cardiovasculares (5,9,22,23). Por otra parte, se encontró que una modificación en la composición de la dieta, y un control en el consumo de energía mejoran las concentraciones de lípi-dos en estos animales produciendo así un beneficio (22,23), ya que en el estudio los caninos alimentados con regímenes hipergrasos presentan valores altos de colesterol total, col-LDL y niveles bajos de col-HDL (9,(19)(20)(21).…”
Section: Discussionunclassified
“…Por eso numerosos análisis identificaron que los perros obesos presentan un col-total, triglicéridos, col-VLDL, col-LDL, más alto que los caninos normales, mientras que el col-HDL es menor en los obesos presentándo-se una situación poco deseable por el riesgo de enfermedades cardiovasculares (5,9,22,23). Por otra parte, se encontró que una modificación en la composición de la dieta, y un control en el consumo de energía mejoran las concentraciones de lípi-dos en estos animales produciendo así un beneficio (22,23), ya que en el estudio los caninos alimentados con regímenes hipergrasos presentan valores altos de colesterol total, col-LDL y niveles bajos de col-HDL (9,(19)(20)(21). Otro factor que se encontró para contrarrestar estos riesgos antes mencionados es el aumento del ejercicio físico de los animales más sedentarios, ya que estudios revelan que los caninos menos activos presentan niveles significativamente altos de col-VLDL y col-LDL en comparación con animales que tienen una rutina de ejercicio o de trabajo (21).…”
Section: Discussionunclassified
“…2 Secondary hypertriglyceridemia, which is the most common form in dogs, usually is the result of an endocrine disorder such as hypothyroidism, diabetes mellitus, or hyperadrenocorticism. 4,5 Other possible causes of secondary hypertriglyceridemia include pancreatitis, 6 obesity, 7,8 lymphoma, 9 or administration of certain drugs (eg, glucocorticoids). 10 A presumptive diagnosis of idiopathic hypertriglyceridemia can only be made when other causes of secondary hypertriglyceridemia have been ruled out.…”
mentioning
confidence: 99%